Cognitive function and quality of life in older adult patients with cochlear implants. (2nd April 2020) - Sorrentino, Tommaso; Donati, Giulia; Nassif, Nader; Pasini, Sara; Redaelli de Zinis, Luca O.
Abstract: Objective: This study aimed to evaluate the benefits of cochlear implant (CI) on speech perception, quality of life (QoL), and cognitive function in profoundly deafened older adults. Design: Longitudinal and cross-sectional cohort study. Study sample: Participants in this study were CI recipients aged 65 years or older (experimental group), CI recipients aged 50 years or younger (control group 1), and normal-hearing participants aged 65 years or older (control group 2). Results: Speech perception significantly improved in both groups of implanted patients (preoperative vs. 1-year median [IQR] sentence recognition: older patients, 0 (0–20) vs. 90 (70–95), p  = 0.001; younger patients, 35 (0–50) vs. 90 (80–100), p  = 0.001). There were no significant differences in QoL (Glasgow Benefit Inventory) between younger and older patients (median [IQR] overall benefit score, 42 (31–64) vs. 53 (39–69), p  = 0.2). Mini-Mental State Examination scores showed no significant differences between elderly CI recipients and normal-hearing participants (median [IQR], 28 (26–28) vs. 28 (27–29), p  = 0.5). Conclusions: Cochlear implantation rehabilitation allows the profoundly deafened older adult to lead a QoL comparable to that of a younger patient. The correlation between hearing restoration and cognitive function preservation in older adults suggest a possible role for CI as a useful resource in limiting age-related cognitive decline.